Utilization of Mobile Health (M-Health) Technology to Increase Coverage and Monitoring of Basic Immunization - Abdullah, Andriyana; Nugraheni, Wahyuningsih Triana; Aldo, Novian (PT. Anagata Sembagi Education, 2025)
Rural areas in Indonesia still face significant challenges in improving maternal and child health, as reflected in high maternal and infant mortality rates (MMR) and infant mortality rates (IMR). Posyandu, as a community-based health service, is a key instrument in reaching vulnerable populations through promotive and preventive approaches. However, Posyandu's effectiveness in various rural areas is strongly influenced by structural factors such as the availability of infrastructure, cadre competence, and village government support, as well as cultural factors such as local values and health literacy. This study aims to evaluate Posyandu's effectiveness in improving maternal and child health in rural areas using a descriptive qualitative approach based on literature studies. Data were obtained from various scientific sources and analyzed using a thematic approach and the PRISMA framework. The study results indicate that Posyandu's success is highly dependent on cross-sector synergy, policy support, and digital transformation through the implementation of e-Posyandu. Geographical constraints, poor cadre training, and minimal community participation are key inhibiting factors. Therefore, a participatory approach, ongoing training, and information technology integration are strategic keys. These findings provide an important basis for evidence-based policy-making in order to strengthen the role of Posyandu as a pillar of basic health services in rural areas.